Anomalous Reaction Pathways to Methane Production in Photocatalytic Ethanol Oxidation - Nasirian, Azam; Sung, Kihyuk; Jang, Hye Young; Yu, Sungju (ACS Applied Materials and Interfaces, 2024)
Photocatalytic reduction reactions occasionally utilize sacrificial agents to scavenge photogenerated holes, thus enhancing the kinetics and efficiency of electron harvesting. However, exploring alternative hole-mediated oxidation reactions and their potential impact on photoredox processes is limited. This study investigates the products resulting from the oxidation of ethanol, a commonly used hole scavenger, and the underlying mechanisms involved. We examine a homogeneous eosin Y photoreaction scheme containing a Cu complex coordinated with an N-heterocyclic carbene, a combination often employed in CO2 conversion. Under visible-light excitation, this photosystem yields methane as an unusual product, alongside acetaldehyde and carbon monoxide. Mechanistic analysis reveals that ethanol undergoes a catalytic cascade involving oxidative processes, C−C bond cleavage, and intermolecular hydrogen atom transfer. Notably, the Lewis-acidic metal center of the Cu complex activates a novel pathway for ethanol oxidation. This work presents the influence of catalyst selection and reaction condition optimization on the emergence of new or unexpected catalytic processes.
Keywords: Cu complexes; Eosin Y; Ethanol oxidation; HAT; Hole scavenger; Methane production; Photo-catalytic; Photocatalytic reduction reaction; Reaction pathways; Sacrificial electron donors; Eosin Y; HAT; hole scavenger; photocatalysis; sacrificial electron donor